Meso‐Cenozoic Tectonic History of the Altai: New Insights From Apatite U‐Pb and Fission Track Thermochronology for the Fuyun Area (Xinjiang, China). Issue 4 (14th April 2023) - Glorie, Stijn; Nixon, Angus L.; Jepson, Gilby; Gillespie, Jack; Warren, Cameron; Meeuws, Fun; Simpson, Alexander; Xiao, Wenjiao
Abstract: The Altai is an enigmatic, relatively young mountain belt with sharp relief (up to 4, 500 m high) that developed thousands of kilometers away from the nearest current plate margins. The Fuyun area, at the interface between the southern margin of the Chinese Altai and the Junggar Basin, represents a key locality for understanding the Meso‐Cenozoic deformation and exhumation history of the Altai. The complex structural architecture of the Fuyun area suggests that multiple deformation events affected the area, which ultimately led to the exhumation of the Altai. Furthermore, the area hosts orogenic‐type mineralization, suggesting a history of fluid alteration. However, in contrast to the well‐constrained Palaeozoic history, the timing of Meso‐Cenozoic deformation, metasomatism and exhumation has not been comprehensively studied. This study presents new apatite U‐Pb, trace element and fission track data for the Fuyun area and integrates these with previous studies for the Altai to shed more light on the Meso‐Cenozoic tectonic history. The apatite U‐Pb dates, associated with LREE‐depleted trace element profiles, suggest that a phase of Middle–Late Jurassic (∼170–160 Ma) metasomatism affected the Keketuohai area, which is potentially linked to the timing of rare‐metal mineralization. The apatite fission track results and thermal history models reveal rapid early Late Cretaceous (∼100–75 Ma) cooling linked to tectonic exhumation throughout the Chinese Altai, associated with distant plate‐margin processes. In addition, samples taken in vicinity to the frontal thrusts of the Altai record evidence for Cenozoic partial resetting of the apatite fission track system. Plain Language Summary: The Altai Mountains are a high elevation, sharp relief mountain belt within central Asia. Despite their location thousands of kilometers from the present day plate margin, the Altai preserve young mountains induced by tectonic forces originating at the plate boundaries. Integrating new low‐temperature data with existing studies reveals extensive uplift of the Altai during the Late Cretaceous, induced by the reactivation of major structures. A subsequent pulse of Cenozoic uplift further developed the topography observed today. In addition to mountain building, alteration of crystalline rocks associated with mineralization has also been observed. The chemical signatures within apatite grains suggests they grew from a fluid that altered the crystalline rocks, which may have links to nearby economic mineralization. Key Points: The Fuyun area records Jurassic metasomatism in apatites corresponding to the timing of hydrothermal rare‐metal mineralization Late Cretaceous rapid cooling is preserved throughout the Altai, coeval with km‐scale deposition of coarse sediments in adjacent basins The Altai shows partial fission track resetting in the Cenozoic during India‐Eurasia convergence, where exhumation has outpaced denudation